2020
DOI: 10.1002/biof.1659
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 aggravates TNF‐α‐induced inflammatory injury via TAK1 pathway in MH7A cells

Abstract: Rheumatoid arthritis (RA) is a common chronic autoimmune disease in women. This research aims to disclose the probable function of lncRNA H19 in MH7A cells. The influences of tumor necrosis factor-α (TNF-α) on cell viability, apoptosis, and inflammatory factor expression were, respectively, detected through cell counting kit-8 (CCK-8), flow cytometry, quantitative reverse transcription polymerase chain reaction (qRT-PCR), enzyme-linked immunosorbent assay (ELISA) assay and Western Blot. The levels of H19 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Overexpression of H19 in PMA-induced THP-1 cells (a common model used to study macrophage activity modulation) upregulates KDM6A and various M1 macrophage-associated factors (particularly CCL8, CXCL9, CXCL10, and CXCL11) which promote M1 macrophage activity and macrophage migration ( 186 ). LncRNA H19 can also aggravate TNF-α-induced inflammatory injury via TAK1 pathway in MH7A cells ( 41 ). LncRNA Hotair exhibited notably high expression levels in the PBMCs and serum exosomes of RA patients, promoting the migration of activated macrophages ( 187 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of H19 in PMA-induced THP-1 cells (a common model used to study macrophage activity modulation) upregulates KDM6A and various M1 macrophage-associated factors (particularly CCL8, CXCL9, CXCL10, and CXCL11) which promote M1 macrophage activity and macrophage migration ( 186 ). LncRNA H19 can also aggravate TNF-α-induced inflammatory injury via TAK1 pathway in MH7A cells ( 41 ). LncRNA Hotair exhibited notably high expression levels in the PBMCs and serum exosomes of RA patients, promoting the migration of activated macrophages ( 187 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, H19 is involved in the STAT3 pathway, which is critical for cancer aggressiveness, potentially impacting the tumor microenvironment. Therefore, the examination of H19 in the context of CRC could yield valuable insights into tumorigenesis, inflammation, and potential therapeutic strategies [ 105 , 106 , 107 ].…”
Section: The Role Of Lncrnas In Tumor–stroma Immune Interplay Via Ext...mentioning
confidence: 99%
“…Both the MAP kinase ERK-1/2 pathway and the phosphatidylinositol 3-kinase pathway affected the H19 RNA expression. The increased sensitivity of overexpressed H19 RNA to starvation/cytokine regulation in RA indicated that embryo genes were involved in the pathogenesis of RA, which reflect the embryonic dedifferentiation and continuous inflammation in synovial tissue (Stuhlmüller et al, 2003;Jarroux et al, 2017;Yang et al, 2020).…”
Section: Lncrnas Involved In Inflammationmentioning
confidence: 99%